Campo a través
La Fura dels Baus distils what they consider essential in this world, their most intimate philosophies. The ideas behind the work, the way trouble is overcome, what is suffered and enjoyed, what excellence means to them; to sum up, how Mugaritz is created and destroyed constantly. Risk is constant, that is the idea behind the title, but it is also proof of the wisdom that comes from the effort and work of many people that have been, are and will be in Mugaritz; a place where the culinary goal has been surpassed by the creative process and its possible variations.--